Magnetic iron oxide nanoparticles encapsulating horseradish peroxidase (HRP): synthesis, characterization and carrier for the generation of free radicals for potential applications in cancer therapy. Issue 112 (23rd November 2016) - Gupta, Nikesh; Gupta, Chetna; Sharma, Sandeep; Rathi, Brijesh; Sharma, Rakesh Kumar; Bohidar, H. B.
Abstract : We report synthesis of iron oxide nanoparticles encapsulating HRP. The average diameter of the particles was around 20 nm. HRP has been used to convert IAA to a toxic oxidized product and its toxic effect has been seen on cancerous cell lines. Abstract : This article reports a method of preparation of iron oxide nanoparticles using a reverse micellar (water-in-oil) approach. We have encapsulated horseradish peroxidase (HRP) in iron oxide nanoparticles. HRTEM, XRD, and DLS analyses showed that the average diameter of these particles was around 20 nm, 20.5 nm, and 30 nm, respectively, and the particles were highly monodispersed with spherical morphology. The entrapment efficiency of HRP was found to be as high as 92%. Practically, the entrapped enzyme shows zero leachability for up to 30 days. Enzyme entrapped in iron oxide nanoparticles followed Michaelis–Menten kinetics and showed higher stability towards temperature change as compared to free enzyme. Entrapped enzyme is stable at up to 65 °C; however, the free enzyme starts to lose its activity above 38 °C. The entrapped enzyme, HRP, has been used to convert a benign prodrug, indole-3-acetic acid (IAA), to a toxic oxidized product, and its toxic effect has been tested on cancerous cell lines through thiazolyl blue tetrazolium blue (MTT) assay. MTT assay on two cancer cell lines revealed that indole acetic acid (IAA), the prodrug alone, had no cytotoxic effect, and it became active only after oxidative decarboxylation by HRP. The benign substrate IAA reaches the cells and is oxidized by HRP. IAA, on reacting with HRP, forms free radicals such as indolyl, skatole and peroxyl radicals. This creates severe oxidative stress in the cancer cells, resulting in cell death.